Itinerários formativos e curriculares na educação de jovens e adultos - Jose Luiz Fazzi (2007)
This thesis on Adult and Youth Education (AYE) aims to analyze schooling routes through and open, dialectical and relational study in its field.As schooling routes, we mean the learning processes present at practices involving teachers, adults, young people, institutions and the education system.Some questions have followed this work: how is the field of Adult and Youth Education constituted from the construction of its political and pedagogical projects blended in educational procedures? More specifically, how do power and knowledge relate at education of young people and adults? What are the roles performed by the curricula set up at AYE schools?We have searched to establish a dialogue among AYE´s social actors and other researchers: Paulo Freire, Gastón Bachelar, Gimeno Sacristán, Carlos Rodrigues Brandão, Miguel Arroyo, including other authors that think education and AYE, therefore accomplishing a qualitative survey.We have analyzed the Workers Education Project developed at E. M. União Comunitária and AYE´s work at E. M. Caio Líbano Soares, in Belo Horizonte. Adult and Youth Education: its name and its insertion in the Brazilian teaching system has brought, from the beginning, a contradiction or, at least, has shown a tension between educating and teaching action. It has com from Lower Income People Education but has tried to be where and when school is. Lower Income People Education wishes to teach, although its goal is to educate. AYE wishes to educate nevertheless, being school, aims to teach. So, curricula and methodologies are founded by Lower Income People Education in a free and open way, while in AYE there is a construction shared with teachers, students, young people and adults and, mainly, with the official system that undertakes to put Education on the way to schooling or to the curricular norms. However AYE may be a possible Utopia searching for a fair and excellent education young people, teenagers and adults.